Effects of hyperoxic gas generator on fatigue recovery after exercise - Muramatsu, S.; Arimoto, M.; Kijima, A. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of the study was to investigate whether the hyperoxic gas generator is effective on the recovery from fatigue after exercise. Summary: The experimental conditions where the proceeding researchers have found the effect were set in this study, but no effect was seen. The main reason for this result is that oxygen concentration actually inhaled was lower than 30% (the reported lowest concentration for the effect). Actually, oxygen concentration measured in the nostril was greatly lower than 30%. Although it is not necessarily clear about the fundamental issues of hyperoxic gas breathing after exercise, the result indicates that the hyperoxic gas generator which is allegedly to supply hyperoxic gas is not effective on the recovery after exercise fatigue in this experimental condition.